2021
DOI: 10.4314/ahs.v21i1.52
|View full text |Cite
|
Sign up to set email alerts
|

Patient patronage and perspectives of traditional bone setting at an outpatient orthopaedic clinic in Northern Tanzania

Abstract: Background: Much of Sub-Saharan Africa meets the rising rates of musculoskeletal injury with traditional bone setting, especially given limitations in access to allopathic orthopaedic care. Concern for the safety of bone setter practices as well as recognition of their advantages have spurred research to understand the impact of these healers on public health. Objectives: Our study investigates the role of bone setting in Tanzania through patient utilization and perspectives. Methods: We surveyed 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…21 Already, studies have shown that healers are available to work with biomedical care providers to improve patient outcomes. 22 Agbodjavou In Kenya, for example, the development of low-cost, highly sustainable home care for people deemed "poor" was based on an approach that involved working with older women in local villages or neighbourhoods. These women participated in a series of intensive workshops designed to equip them with the knowledge and skills to provide terminal home care to all members of their community, regardless of the patient's status.…”
Section: Palliative and End-of-life Support: An Attempt At A Concepti...mentioning
confidence: 99%
“…21 Already, studies have shown that healers are available to work with biomedical care providers to improve patient outcomes. 22 Agbodjavou In Kenya, for example, the development of low-cost, highly sustainable home care for people deemed "poor" was based on an approach that involved working with older women in local villages or neighbourhoods. These women participated in a series of intensive workshops designed to equip them with the knowledge and skills to provide terminal home care to all members of their community, regardless of the patient's status.…”
Section: Palliative and End-of-life Support: An Attempt At A Concepti...mentioning
confidence: 99%